2013
DOI: 10.1149/05006.0377ecst
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Formation of Ordered Pore Arrays in InP in KCl

Abstract: Pores are formed electrochemically in n-InP in KCl electrolytes with concentrations of 2 mol dm-3 or greater. The pore morphology is similar to what is seen in other halide-based electrolytes. At low potentials, crystallographically oriented (CO) pores are formed. At higher potentials, current-line oriented (CLO) pores are formed. Crystallographically oriented pore walls are observed for both pore morphologies. When formed at a constant current, potential oscillations are observed which have been correlated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Nanopore formation due to electrochemical etching occurs in a range of semiconductors from Si to InP [2][3][4][5][6][7][8][9] and it is quite common for such pores to propagate along preferential directions. These directions and the pore morphology have been shown to be affected by a range of parameters including temperature, 10 composition 11,12 and concentration 13 of electrolyte, and type, 14 orientation 15 and doping density 16 of the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Nanopore formation due to electrochemical etching occurs in a range of semiconductors from Si to InP [2][3][4][5][6][7][8][9] and it is quite common for such pores to propagate along preferential directions. These directions and the pore morphology have been shown to be affected by a range of parameters including temperature, 10 composition 11,12 and concentration 13 of electrolyte, and type, 14 orientation 15 and doping density 16 of the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 It has been recently demonstrated that porous dissolution can also be achieved at neutral solution in presence of Cl − . 16,17 Finally, a nucleophilic substitution mechanism has been proposed to explain the pore growth on III-V crystals.…”
Section: 10mentioning
confidence: 99%
“…14,15 It has been recently demonstrated that porous dissolution can also be achieved at neutral solution in presence of Cl − . 16,17 Finally, a nucleophilic substitution mechanism has been proposed to explain the pore growth on III-V crystals.18-20 It demonstrates that both physical and chemical models must be considered when dealing with porous etching.Investigations on the chemical, electrochemical and photoelectrochemical uniform etching of InP have led to various possible mechanisms. Although 6 or 8 charge mechanisms are usually admitted, the dissolution valence analytically determined by measuring the indium ion concentration in the etching solution, using atomic absorption spectroscopy (AAS) or inductively coupled plasma emission spectrometry (ICP-ES), varies from 3 to 12.…”
mentioning
confidence: 99%
“…Nanopore formation due to electrochemical etching has been demonstrated in a range of semiconductors from Si to InP(1-12). The morphology of these porous layers can vary wildly between different semiconductors (13), and for an individual semiconductor with the variation of temperature (14), composition (15,16) and concentration (17) of electrolyte, and orientation (18) and doping density (19) of the substrate. Many different pore morphologies have been observed and several models have been proposed (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) to explain them.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously investigated (14,15,(33)(34)(35)(36)(37)(38)(39) the early stages of pore formation in InP in aqueous KOH electrolytes. Pores originate from etch pits in the electrode surface and propagate along <111>A directions to form porous domains beneath a thin dense (i.e.…”
Section: Introductionmentioning
confidence: 99%